Outthink the competition how a new generation of strategists see options others ignore - Krippendorff, Kaihan. (Wiley, 2012)
"A new generation of leader is emerging, the next generation business strategist: "Outhinkers."They are entrepreneurs and corporate managers with a new playbook. They see opportunities others ignore, challenge dogma others accept as truth, rally resources others cannot influence, and unleash new strategies that disrupt their markets.Outthink the Competition proves that business competition is undergoing a fundamental paradigm shift and that during such revolutions, outthinkers beat traditionalists. Outthink the Competition presents stories of breakthrough companies like Apple, Google, RIM, and Rosetta Stone whose stunning performances defy traditional explanation and will inspire readers to outthink the competition. Core concepts in the book include: Eight Dimensions of Disruption The Outthinker Playbook Adopting Five Habits of the Outthinker The Outthinker Process "--